The effectiveness of pure stichopus horrens (Gamat) extract toothpaste in reducing plaque induced gingivitis post orthodontic bond-up: a triple-blinded randomized controlled trial - Abu Bakar, Noraini; Muhammad Ali, Suhaila; Nasir, Siti Hajjar; Jayah, Nurul Idayu; Kharuddin, Azrul Fazwan (2018)
Introduction: Gingivitis is one of the commonest problems faced by fixed orthodontic patients as there is close relation between the appliances to gingival sulcus. Stichopus horrens (SH) is a sea cucumber from the Indo-Pacific that has medical healing properties which have been traditionally used for years. Materials and methods: A single-centred; triple-blinded randomized controlled trial conducted on 40 fixed-orthodontic patients. Subjects were randomly assigned to one of the four groups with toothpaste which has concentration of SH extract of 0%, 3%, 6% or 9%. The statistician, the patients and the researchers involved in sample taking were kept blinded from the allocation. Gingival Index (GI) and Bleeding on Probing (BOP) for each group were taken at day 0,7,14 and 30 to assess the gingival health. Results: 9% of SH-containing toothpaste (SHCT) showed most substantial result as there were significance difference of GI (p= 0.020) from Day 7 to 14 and from Day 0 to 14(p=0.020). There was also significance difference of BOP from Day 0 to 14(p=0.022) and from Day 0 to 30(p=0.027). Significant difference was seen in 3% of SHCT group with the decrease of GI (p=0.004) from Day 1 to 14. There was no significant difference noted for 0% and 6% SHCT. Conclusions: SH have healing properties in plaque-induced gingivitis patients. The 9% SH-containing toothpaste is the most effective concentration to reduce the gingival inflammation